Nutritional Study of RUTF Snack Bar from Jackfruit Seed Flour, Durian Seed Flour, and Cempedak Seed Flour - Indriyanti Putri, Tiara; F. Rosida, Dedin (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Ready-to-Use Therapeutic Food (RUTF) is a nutrient-dense, ready-to-eat product with a long shelf life, making it highly effective for emergency nutrition interventions and malnutrition recovery programs. This study aims to determine the optimal combination of seed-based flour and mackerel fish flour to enhance the physicochemical and organoleptic properties of RUTF snack bars. Jackfruit, durian, and cempedak seeds were selected for their rich nutritional profiles, including protein, fiber, vitamins, and minerals. Mackerel fish flour, with a high protein content (72.96%), was incorporated to improve the protein quality of the formulation. A completely randomized design (CRD) with a factorial arrangement was applied, consisting of two factors: the ratio of fish flour to seed flour (5:95, 10:90, 15:85) and the type of seed flour (jackfruit, durian, cempedak), with two replications. Data were analyzed using ANOVA at a 5% significance level, followed by the DMRT test for significant interactions. The best formulation was achieved using 85% durian seed flour and 15% mackerel fish flour, yielding a moisture content of 2.88%, ash content of 4.01%, protein content of 41.53%, fat content of 44.84%, crude fiber content of 26.23%, starch content of 43.74%, amylose content of 20.33%, carbohydrate content of 9.60%, hardness of 134.2 gf, and total caloric value of 608 kcal. These findings highlight the potential of seed-based flours and fish protein in developing nutritious, shelf-stable RUTF snack bars. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 3: Good Health and Well-SDG 13: Industry, Innovation, and Infrastructure SDG 15: Responsible Consumption and Production